Design and development of solar energy system for use in home in Singapore - Mak, Choy Weng. (2012)
As conventional fossil-fuel energy sources diminish and the world becomes increasingly aware of and concerned about the environmental footprints of acid deposition and global warming, renewable energy sources like solar, wind, tidal, and geothermal energies are increasingly viewed as alternative energy sources which can be harnessed to meet future energy needs.